Phytoclimatic mapping of exoplanets. Issue 1 (19th February 2020) - Stevenson, David S.
Abstract: The concept of exoplanetary habitability is evolving. The driving force is a desire to define the biological potential of planets and identify which can host complex and possibly intelligent life. To assess this in a meaningful manner, climate models need to be applied to realistic surfaces. However, the vast majority of climate models are developed using generic aquaplanet, or swamp planet, scenarios that provide uniform, surface frictional coefficients. However, aside from planets with largely uniform oceans, these models are not obviously useful when it comes to understanding the impact of climate on biodiversity. Here, we show that contrary to expectation, the aquaplanet models can be directly applied to planets with a variety of land areas, with little need for modification. Using this premise, this paper provides a simple mathematical framework that may be applied to more complex planetary surfaces and identifies the majority of the climate-model components that are needed to accurately determine the biological potential of habitable exoplanets. As a proof-of-concept, an available climate model for Proxima b is used to determine its biological potential, given a suitable atmosphere.